Effect of different shapes of steel fibers and palygorskite-nanofibers on performance of ultra-high-performance concrete - Yingying Huang; Dewen Kong; Yi Li; Shenghui Zhou; Jing Shu; Bing wu (Scientific Reports, 2024)
Abstract Herein, a practical ultra-high-performance concrete (UHPC) was created by adding two different shapes of steel fibers and curing them at ambient temperature using palygorskite-nanofiber (PN) as the modifier. The compressive strength, flexural strength, water absorption capacity, and porosity were analyzed to determine the effects of the steel fibers and PNs on the UHPC mechanical and physical properties. The steel fibers and PNs were found to improve these properties. The UHPC mechanical properties were outstanding at 1.5% fiber dosage, while physical properties were excellent at 1.0% fiber dosage. The mechanical and physical characteristics of UHPC were preferably at a PN dosage of 0.2% and the fiber dosage of 1.0%. The compressive and flexural strengths of straight-steel-fiber UHPC were 145.57 and 19.67 MPa, respectively, i.e., 42.0 and 109.4% higher than those of the reference specimens (i.e., those without fibers or PNs); the water absorption capacity and porosity decreased by 50.1 and 60.7%, respectively. The compressive and flexural strengths of hooked-end-steel-fiber UHPC were 18.3 and 96.0% higher than those of the reference specimens, respectively, and the water absorption capacity and porosity decreased by 43.2 and 29.8%, respectively. These results could provide vital information for the promotion and practical application of UHPC.